Cardiorenal Involvement in Metabolic Syndrome Induced by Cola Drinking in Rats: Proinflammatory Cytokines and Impaired Antioxidative Protection - Matilde Otero-Losada; Hernán Gómez Llambí; Graciela Ottaviano; Gabriel Cao; Angélica Müller; Francisco Azzato; Giuseppe Ambrosio; José Milei (Mediators of Inflammation)
We report experimental evidence confirming renal histopathology, proinflammatory mediators, and oxidative metabolism induced by cola drinking. Male Wistar rats drank ad libitum regular cola (C, n=12) or tap water (W, n=12). Measures. Body weight, nutritional data, plasma glucose, cholesterol fractions, TG, urea, creatinine, coenzyme Q10, SBP, and echocardiograms (0 mo and 6 mo). At 6 months euthanasia was performed. Kidneys were processed for histopathology and immunohistochemistry (semiquantitative). Compared with W, C rats showed (I) overweight (+8%, p<0.05), hyperglycemia (+11%, p<0.05), hypertriglyceridemia (2-fold, p<0.001), higher AIP (2-fold, p<0.01), and lower Q10 level (−55%, p<0.05); (II) increased LV diastolic diameter (+9%, p<0.05) and volume (systolic +24%, p<0.05), posterior wall thinning (−8%, p<0.05), and larger cardiac output (+24%, p<0.05); (III) glomerulosclerosis (+21%, p<0.05), histopathology (+13%, p<0.05), higher tubular expression of IL-6 (7-fold, p<0.001), and TNFα (4-fold, p<0.001). (IV) Correlations were found for LV dimensions with IL-6 (74%, p<0.001) and TNFα (52%, p<0.001) and fully abolished after TG and Q10 control. Chronic cola drinking induced cardiac remodeling associated with increase in proinflammatory cytokines and renal damage. Hypertriglyceridemia and oxidative stress were key factors. Hypertriglyceridemic lipotoxicity in the context of defective antioxidant/anti-inflammatory protection due to low Q10 level might play a key role in cardiorenal disorder induced by chronic cola drinking in rats.